2007
DOI: 10.1089/apc.2007.9989
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Engaging Socially Marginalized HIV-Positive Persons in Primary Care

Abstract: This paper examines factors associated with engaging socially marginalized HIV-positive persons in primary care using interview and chart review data from 984 clients presenting for services at 10 agencies participating in a multisite demonstration project. The sample was predominantly minority, and many reported drug and mental health problems as well as housing instability. At baseline, roughly half of the participants were engaged in HIV primary care; the other participants were either not at all engaged in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 14 publications
3
72
0
Order By: Relevance
“…Though retention and suppression are often treated separately in the literature, 11,[16][17][18][19][20]35,36 this study examined both measures by focusing on an impoverished, vulnerable prospective cohort of WOC. For these women, our findings suggest that retention and viral suppression were influenced by different factors, and that interventions seeking to improve retention may require program components and strategies that differ from interventions aiming to improve viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Though retention and suppression are often treated separately in the literature, 11,[16][17][18][19][20]35,36 this study examined both measures by focusing on an impoverished, vulnerable prospective cohort of WOC. For these women, our findings suggest that retention and viral suppression were influenced by different factors, and that interventions seeking to improve retention may require program components and strategies that differ from interventions aiming to improve viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Some studies using different age ranges for analysis found no difference in linkage in younger adults. 35,[43][44][45] However, combining published data from these studies (Table 1), we estimate that 62% of newly diagnosed HIV-infected adolescents and young adults in the United States link to care within the first 6-12 months.…”
Section: Linkage To Carementioning
confidence: 97%
“…11 For example, suboptimal HIV health care utilization patterns are associated with racial=ethnic minority status, 9,[15][16][17][18] economic and health insurance difficulties, [19][20][21][22] engaging in illicit drug or alcohol use, [23][24][25][26][27] having unstable housing, 28,29 and difficulty developing positive relationships with a primary care provider. [30][31][32][33][34][35][36][37][38] Because barriers to health care utilization vary by population, it is crucial for providers and interventionists to identify key barriers that are specific to the disadvantaged populations that they target.…”
Section: Introductionmentioning
confidence: 99%